Bioactive potential: The medicinal properties of truffles - Akyüz, Mehmet; Kirbağ, Sevda (CRC Press, 2025)
Macrofungi have been a source of fascination for humans since ancient times due to their ecological, environmental, health, and nutritional benefits. They are particularly important to many indigenous peoples, providing daily sustenance and commercial income (Li et al., 2021; Pérez-Moreno et al., 2021; Niego et al., 2023). For centuries, people have collected and consumed wild edible mushrooms for food and medicinal purposes. Certain macrofungal species also hold cultural significance in religious rituals, handicrafts, myths, and beliefs. This tradition dates back to many ancient civilizations, including Greek, Egyptian, Roman, Chinese, and Mexican. These civilizations were aware of the therapeutic benefits of mushrooms and used them in various ways (Dugan, 2011; Martins, 2016). Mushrooms were considered a delicacy by early civilisations such as Egyptian(Pharaohs), and Roman. While the ancient Greeks believed that mushrooms gave warriors strength in battle, the Romans saw them as the 'food of the gods' created by the lightning struck by Jupiter. The Egyptians thought they were a gift from the 'god Osiris'. The Chinese considered mushrooms to be a health food and referred to them as an 'elixir of life'. Similarly, Mexicans used mushrooms as a 'gift of love' in religious ceremonies (Manzi et al., 1999; Miles and Chang, 2004; Valverde et al., 2015). Mushrooms have attracted much attention due to their taste, nutritional value, and potential medicinal benefits. They are commonly referred to as 'superfoods' and are considered an important part of a healthy diet (Kour et al., 2022). These objective and factual characteristics make them a popular choice for consumption. © 2025 Kandikere R. Sridhar and Sunil K. Deshmukh. All rights reserved.